INSAR Special Interest Group Report: Stakeholder Perspectives on Priorities for Future Research on Autism, Sexuality, and Intimate Relationships. Issue 8 (25th June 2020) - Dewinter, Jeroen; van der Miesen, Anna I. R.; Holmes, Laura Graham
Abstract: The number of empirical studies on sexuality and intimate relationships in autistic people has grown over the last years with the increasing awareness that sexuality and intimate relationships are an important part of life and well‐being for autistic people. Further, expression and enjoyment of sexuality is a fundamental, basic human right. This paper reports on needs for future research in this area based on the input of autistic adults, researchers, and other stakeholders (e.g., parents and professionals). Utilizing the nominal group technique, 65 individuals participated in eight groups in which they brainstormed on research questions they deemed most important. Responses were categorized into themes and ranked according to importance based on the level of priority attributed by participants. Findings suggest that future research should focus on developing ways to support sexual and relationship well‐being and getting a better understanding of sexuality and relationships in autistic people. Also, attention was drawn to the need for studying the influence of stereotypical societal views, and stigma. Finally, the importance of participatory research to include perspectives of autistic people in research and practice was stressed. Lay Summary: Sexuality and romantic relationships are part of daily life for most people, including autistic people. For this study, groups of autistic people, professionals, and autism researchers discussed which research on autism, sexuality, and relationships is needed and can help autistic adolescents and adults. The group discussions revealed that more research is needed on how to support well‐being relating to romantic relationships and sexuality in autistic people and how the people around them can contribute to this. Therefore, we also need to learn more about how autistic people of all ages and throughout their lives experience sexuality and relationships. Finally, the need for attention to the role of stereotypical ideas and stigma about autism, sexuality, and relationships was pointed out. Attention to the experiences of autistic people can help professionals, researchers, and policy makers to offer and organize attuned support and do relevant research. Autism Res 2020, 13: 1248–1257 . © 2020 The Authors. Autism Research published by International Society for Autism Research published by Wiley Periodicals LLC.